Urgensi Fatwa Mui dalam Pembangunan Sistem Hukum Ekonomi Islam di Indonesia - Abidah Masrurah; Muzalifah Muzalifah (Indonesian Journal of Shariah and Justice, 2022)
A fatwa is not the same as a positive regulation that limits power to all citizens, but a fatwa can have limiting powers once it is converted into a legal guideline. The fatwas given by the DSN-MUI (General Sharia Committee of the Indonesian Ulema Council) amounted to around 107 fatwas and have made a positive commitment to the guidelines for the sharia monetary regulatory framework. The DSN-MUI fatwa is an important part of the laws and regulations of the Unitary State of the Republic of Indonesia which is guided by Pancasila, the main statute of which is Belief in One Supreme God and one of the living rules is Islamic law. This standardized juridical examination technique is carried out with an astonishing logic methodology, which describes methodically, earnestly and precisely, the real factors and problems considered related to valid hypotheses and with (1) a rule approach, (2) a series of experiences (verifiable methodology), (3) political methodology (political methodology). In addition, the information obtained is broken down in a subjective juridical manner by considering the material of the entire legal instrument and then described.